(3efbHg dCejQ GdeDefjf Ydi QVi Gddg Yfgs - (3Ydj Hf GdMSjf Hf Ydj GdeDOH Hf GdUHGZs
(3ChdgG (B:s
(3Qhi CHh LYaQ eMeO Hf Ydi Hf GdMSjf bGd deG LdS Ydi Ydi GdNdGaI hHGjYI GdfGS NQL EdiGdeSLO eJYeekG HYeGeI QShd Gddg dGHSG HQOI QShd Gddg s
(3BNQgG (B:s
(3Ke bGd eYGTQ GdfGS CTgOhG EfgG aQNG QShd Gddg hhOjYJg GdJi ESJhOYfjgG hEfG ESJhOYcehgG eYGTQ GdfGS hQShd Gddg SGFdce YfgG hUdi Gddg Ydi eMeO hBdg hSde JSdjekG Je hGdMeO ddg QH GdYGdejf hdG Mhd hdG bhI EdG HGddg GdYdi GdYXje s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B9s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje dGYGeI (B_ (3GdfLa (B(369) s
Keywords: (3GdeLGejYs